2008
DOI: 10.1373/clinchem.2007.097568
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Characteristics of Commercial Cardiac Troponin I and T Immunoassays in Serum from Rats, Dogs, and Monkeys with Induced Acute Myocardial Injury

Abstract: BACKGROUND:Information is needed regarding analytical characteristics of cardiac troponin (cTn) assays used in preclinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 23 publications
0
57
0
4
Order By: Relevance
“…Challenges remain with regard to preclinical applications, including assessment of a suitable cutoff for irreversible myocardial injury, optimal timing of sample collection (Adamcova et al 2005), relatively limited data sets for animals, and lack of standardization between various immunoassays available to measure cTnI concentration. Important differences exist in species-specific cross-reactivity of the antibodies used in the assays available for the measurement of cTnI concentrations in laboratory rats, dogs, and monkeys, as well as the precision and accuracy of the measurements (Apple et al 2008). There is little information available regarding the use of these same assays in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges remain with regard to preclinical applications, including assessment of a suitable cutoff for irreversible myocardial injury, optimal timing of sample collection (Adamcova et al 2005), relatively limited data sets for animals, and lack of standardization between various immunoassays available to measure cTnI concentration. Important differences exist in species-specific cross-reactivity of the antibodies used in the assays available for the measurement of cTnI concentrations in laboratory rats, dogs, and monkeys, as well as the precision and accuracy of the measurements (Apple et al 2008). There is little information available regarding the use of these same assays in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In the nephrotoxicity biomarker project, the committee assembled data related to urinary markers of nephrotoxicity that had been described and used by others in the field. In 2008 and 2009, the committee worked closely with regulatory agencies to review the literature and address clarifying questions surrounding a proposed set of urinary biomarkers [52]. In 2010 the FDA released a final decision approving the biomarkers and the context in which they can be used [53].…”
Section: Discussionmentioning
confidence: 99%
“…We supposed that cTnT analyses had an insufficient sensitivity in the present study. Moreover, Apple et al [36] reported that cTnI assays providing a measurable signal in the absence of a cTnT signal in rat, dog and monkey. Additionally, cTnI is more sensitive than cTnT and its values 3-7-fold higher than from cTnT with any given heart damage [37] .…”
Section: Güneş Uyanik Eren Ki̇bar Aslan Onmazmentioning
confidence: 99%